Jual Beli Hak Atas Tanah Dengan Pemberian Kuasa Menurut Hukum Perdata - Atika Sari; Jenny Kristiana Matuankotta; Novyta Uktolseja (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The form of granting power is carried out in various ways, orally granting power of attorney is considered valid according to the Civil Code even though the strength of the law is weak. The practice in society is often between the authorizer and the beneficiary of one of his parties acting outside the authority or rights and obligations that have been given so as to make one of them feel aggrieved.Purposes of the Research: Analyzing and reviewing the position of the buyer who provides legal power and protection for the actual buyer. Methods of the Research: This research is included in normative legal research, namely research examining various positive legal provisions, various legal principles, legal principles and doctrines to answer legal issues faced by.Results of the Research: The results of the study show that the orally granting of power of attorney is valid, the strength of the law is weak but does not rule out the possibility that it can be proven in accordance with the provisions of the Civil Procedure Law, proof of land purchase transactions is an important evidence that shows the subject of the transaction, both sellers, buyers and third parties, so that in the proof of payment must be clearly stated, to avoid the possibility of harming interested parties because of this proof of payment can be clearly proven its position.